Hexacoordinate Nickel(II)/(III) Complexes that Mimic the Catalytic Cycle of Nickel Superoxide Dismutase1. Issue 38 (23rd July 2014) - Chatterjee, Sudip K.; Maji, Ram Chandra; Barman, Suman Kumar; Olmstead, Marilyn M.; Patra, Apurba K.
Abstract A functional model complex of nickel superoxide dismutase (NiSOD) with a non‐peptide ligand which mimics the full catalytic cycle of NiSOD is unknown. Similarly, it has not been fully elucidated whether NiSOD activity is a result of an outer‐ or inner‐sphere electron‐transfer mechanism. With this in mind, two octahedral nickel(II)/(III) complexes of a bis‐tridentate N2S donor carboxamide ligand, N‐2‐phenylthiophenyl‐2′‐pyridinecarboxamide (HLPh), have been synthesized, structurally characterized, and their SOD activities examined. These complexes mimic the full catalytic cycle of NiSOD. Electrochemical experiments support an outer‐sphere electron‐transfer mechanism for their SOD activity.